+0  
 
0
286
1
avatar

why is root 3i multiplied by - root 3i equal to 3?     √3i x (-√3i) = 3

Guest Jan 6, 2015

Best Answer 

 #1
avatar+91451 
+10

$$i=\sqrt{-1}$$       It is an imaginary number.

 

$$i\times i = \sqrt{-1}\times \sqrt{-1} = -1$$

SO

 

√3i x (-√3i) 

 

$$\\=\sqrt3\times i\times -\sqrt3\times i\\
=-\sqrt3\times\sqrt3\times i\times i\\
=-\sqrt9\times i\times i\\
=-3\times -1\\
=3$$

Melody  Jan 7, 2015
Sort: 

1+0 Answers

 #1
avatar+91451 
+10
Best Answer

$$i=\sqrt{-1}$$       It is an imaginary number.

 

$$i\times i = \sqrt{-1}\times \sqrt{-1} = -1$$

SO

 

√3i x (-√3i) 

 

$$\\=\sqrt3\times i\times -\sqrt3\times i\\
=-\sqrt3\times\sqrt3\times i\times i\\
=-\sqrt9\times i\times i\\
=-3\times -1\\
=3$$

Melody  Jan 7, 2015

10 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details